Compromised fidelity of endocytic synaptic vesicle protein sorting in the absence of stonin 2 - Kononenko, Natalia L. (National Academy of Sciences, 2013)
Neurotransmission depends on the exocytic fusion of synaptic vesicles (SVs) and their subsequent reformation either by clathrin-mediated endocytosis or budding from bulk endosomes. How synapses are able to rapidly recycle SVs to maintain SV pool size, yet preserve their compositional identity, is poorly understood. We demonstrate that deletion of the endocytic adaptor stonin 2 (Stn2) in mice compromises the fidelity of SV protein sorting, whereas the apparent speed of SV retrieval is increased. Loss of Stn2 leads to selective missorting of synaptotagmin 1 to the neuronal surface, an elevated SV pool size, and accelerated SV protein endocytosis. The latter phenotype is mimicked by overexpression of endocytosis-defective variants of synaptotagmin 1. Increased speed of SV protein retrieval in the absence of Stn2 correlates with an up-regulation of SV reformation from bulk endosomes. Our results are consistent with a model whereby Stn2 is required to preserve SV protein composition but is dispensable for maintaining the speed of SV recycling.